2015
DOI: 10.1155/2015/159458
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Different Thin Film Module Technologies

Abstract: For a complete quality control of different thin film module technologies (a-Si, CdTe, and CIS) a combination of fast and nondestructive methods was investigated. Camera-based measurements, such as electroluminescence (EL), photoluminescence (PL), and infrared (IR) technologies, offer excellent possibilities for determining production failures or defects in solar modules which cannot be detected by means of standard power measurements. These types of optical measurement provide high resolution images with a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Moreover, the haziness that is a type of discoloration has been observed in the modules which can create shading and reduce the module performance. However, it should be noted that thin‐film technologies always have a high degradation in its initial phase due light soaking effect before it becomes stable and the same can also be seen from this study 66,67 . Some researchers have also established this fact such as the Ye et al 68 have reported high degradation rate of 2% during the first year of operation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the haziness that is a type of discoloration has been observed in the modules which can create shading and reduce the module performance. However, it should be noted that thin‐film technologies always have a high degradation in its initial phase due light soaking effect before it becomes stable and the same can also be seen from this study 66,67 . Some researchers have also established this fact such as the Ye et al 68 have reported high degradation rate of 2% during the first year of operation.…”
Section: Resultssupporting
confidence: 78%
“…The white spots have been observed on both water‐ and land‐mounted modules. These white spots are referred to as shunts in the CdTe module and may be caused by the presence of defects and impurities during the manufacturing process of the CdTe module 66 . Due to exposure of CdTe modules to the outdoor environment, these defects appear and can be identified visually which eventually decreases FF and increases degradation.…”
Section: Resultsmentioning
confidence: 99%
“…It is a non-destructive measurement technique, which provides fast, real-time and two-dimensional distributions of characteristic features from PV modules [17][18][19]. In addition, IRT can be performed in illuminated or dark conditions [16,[20][21][22].…”
Section: Irt Versus El Inspectionsmentioning
confidence: 99%
“…Although it has been traditionally applied only with the PV plant in operation, which has the great advantage of not losing energy, it can also be applied while injecting current to the modules in the fourth quadrant, simultaneously or subsequent to EL inspections. Some authors term these two kinds of thermographic inspections as outdoor (illuminated) and indoor (dark) conditions, respectively [ 10 , 27 , 28 , 29 , 30 ]. However, novel research in PV systems propose the use of a power inverter with bidirectional power flow capability for utility-scale PV plants maintenance, using the EL technique, together with the flexibility provided by this type of devices [ 19 ].…”
Section: Introductionmentioning
confidence: 99%